VALIDITAS MEDIA PEMBELAJARAN FLASHCARD BERBASIS AUGMENTED REALITY (AR) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VI SEKOLAH DASAR - Wanda Cahya Dwi Tanti; Sita Isna Malyuna; Wendri Wiratsiwi (Universitas Negeri Medan, 2026)
Quality of education depends on student learning outcomes during the learning process, the purpose of the study is to measure the level validity of Augmented Reality (AR) based Flashcard media to improve the learning outcomes of sixth grade elementary school students in the problems faced during the science learning process, where student learning outcomes are the main focus of research that important to improve results. The Research and Development (R&D) method is research with the ADDIE approach. Data acquisition techniques in the study are observation, interviews, and expert validation. The results of the media expert validator reached a percentage of 85% which is categorized as